2021
DOI: 10.1017/jfm.2020.1185
|View full text |Cite
|
Sign up to set email alerts
|

Flow-roughness heterogeneity: critical obliquity and salient parameters

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…The secondary vortex structure thus obtained is consistent with experimental observations of flows over damaged turbine blades [78,79]. In these studies, strips with low and high flow velocities were found out, which can be related with the presence of large-scale secondary flows [68,84]. As…”
Section: Secondary Flows Near Rough Surfacessupporting
confidence: 88%
“…The secondary vortex structure thus obtained is consistent with experimental observations of flows over damaged turbine blades [78,79]. In these studies, strips with low and high flow velocities were found out, which can be related with the presence of large-scale secondary flows [68,84]. As…”
Section: Secondary Flows Near Rough Surfacessupporting
confidence: 88%
“…2013; Barros & Christensen 2014; Anderson et al. 2015 a ; Pathikonda & Christensen 2017; Yang & Anderson 2017 a ; Awasthi & Anderson 2018; Zheng & Anderson 2021). Results will demonstrate that, indeed, - or -type roughness can regulate the polarity of roughness-driven secondary flows, where the former and latter induce upwelling and downwelling aloft streamwise-aligned roughness ‘rows’, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the present context, the relative excesses occur above the streamwise-aligned rows. For brevity, and because has been shown in complementary prior articles (Zheng & Anderson 2021), contours are not shown here. We have prepared targeted results of total streamwise–wall-normal turbulent stress, which is indicative of in rough wall channel turbulence.…”
Section: Resultsmentioning
confidence: 99%
“…TBL flows over various spanwise-heterogeneous rough walls have received a great deal of attention in recent years (e.g. Nugroho et al 2013, Barros and Christensen 2014, Anderson et al 2015, Kevin et al 2017, Bai et al 2018, 2021, Medjnoun et al 2020, Xu et al 2020, Zheng and Anderson 2021. Compared with that over the smooth wall, TBL flows over the spanwise-heterogeneous rough walls are characterized by large variations of flow statistics along the spanwise direction.…”
Section: Introductionmentioning
confidence: 99%